Towards Measuring Air Quality Index with Country and States Granularity from Sentinel-5 Data - Cuno, Jordan Salas; Conci, Aura; Silva-Júnior, Andouglas G. da; Gonçalves, Luiz M. G. (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2022: Anais Estendidos da XXXV Conference on Graphics, Patterns and ImagesDO - 10.5753/sibgrapi.est.2022.23282, 2022)
One of the topics that have been recently discussed with greater emphasis is air quality, not only because it is a topic directly related to climate change and the greenhouse effect, but also because it has a strong link in the transmission of respiratory diseases. Low-quality indices of air can worsen the symptoms of patients with the COVID-19 pandemic, being one of the most recent examples. Being able to identify and monitor air quality in different geographic regions of Brazil will provide information on possible measures to be taken by authorities and citizens in general. Air quality indices are currently monitored by some entities using technology of sensors strategically installed at fixed points in cities. Another type of technology available is the high-resolution spectrometer system installed on satellites that constantly monitor the surface of the planet. Sentinel-5 is one of these satellites that generates a large amount of data for climate monitoring and that is used in this research. Basically, in this work, we propose a system that takes data from the Sentinel-5 in order to provide a measure of air quality to be used in the prediction of the pandemic dynamics.